Phototoxic Activity and DNA Interactions of Water‐Soluble Porphyrins and Their Rhenium(I) Conjugates. Issue 11 (2nd September 2015) - Mion, Giuliana; Gianferrara, Teresa; Bergamo, Alberta; Gasser, Gilles; Pierroz, Vanessa; Rubbiani, Riccardo; Vilar, Ramon; Leczkowska, Anna; Alessio, Enzo
Abstract: In the search for alternative photosensitizers for use in photodynamic therapy (PDT), herein we describe two new water‐soluble porphyrins, a neutral fourfold‐symmetric compound and a +3‐charged tris‐methylpyridinium derivative, in which either four or one [1, 4, 7]‐triazacyclononane (TACN) units are connected to the porphyrin macrocycle through a hydrophilic linker; we also report their corresponding tetracationic Re I conjugates. The in vitro (photo)toxic effects of the compounds toward the human cell lines HeLa (cervical cancer), H460M2 (non‐small‐cell lung carcinoma), and HBL‐100 (non‐tumorigenic epithelial cells) are reported. Three of the compounds are not cytotoxic in the dark up to 100 μm, and the fourfold‐symmetric couple revealed very good phototoxic indexes (PIs). The intracellular localization of all derivatives was studied in HeLa cells by confocal fluorescence microscopy. Although low nuclear localization was observed for some of them, it still prompted us to investigate their capacity to bind both quadruplex and duplex DNA; we observed significant selectivity in the tris‐methylpyridinium derivatives for G‐quadruplex interactions. Abstract : Cancer brought to light : Two water‐soluble porphyrins containing four or one [1, 4, 7]‐triazacyclononane (TACN) moieties are described, along with their corresponding tetracationic rhenium(I) conjugates. The in vitro (photo)toxic effects of these compounds toward human cervical cancer cells (HeLa), non‐small‐cell lung carcinoma cells (H460M2) and non‐tumorigenic epithelial cells (HBL‐100), their intracellular localization in HeLa cells, and the quadruplex and duplex DNA binding of these compounds are reported.